PERANAN CORPORATE SOCIAL RESPONSIBILITY PT. JAYA MANDIRI SUKSES DALAM MENINGKATKAN PEMBANGUNAN DI DESA MUARA LEKA KECAMATAN MUARA MUNTAI - Ripka Ripka; Achmad Djumlani; Anwar Alaydrus (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This study aims to determine the role of Corporate Social Responsibility (CSR) in improving rural community development in Muara Leka Village, Muara Muntai District. This study used a qualitative model and analyzed using an interactive data model. The results showed that in the distribution of CSR funds PT. Jaya Mandiri Sukses has been going quite well, but an evaluation is needed. CSR PT. Jaya Mandiri Sukses is divided into three: CSR infrastructure development, human resource development, and community empowerment.Keywords: CSR, development, role